Antenatal Depression among Pregnant Women at a Tertiary Care Hospital - Sumyya Ahmed, Shazia Jabbar, Marvi Bozdar, Saima Ali, Komal Memon, Amina Begum (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Depression is among the most prevalent psychiatric disorders affecting women. Depressive disorders are predicted to be the second leading cause of global disability burden by 2020. The risk of depression increased significantly during pregnancy and clinically significant depressive symptoms are common in mid and late trimesters. The purpose of present study is to determine the frequency of antenatal depression, so that better strategies and early management was recommended in such patients to reduce frequency of depression. Objectives: To determine the frequency of antenatal depression among pregnant women presenting to a tertiary care hospital. Study Settings: This Cross sectional Study was conducted at the Department of obstetrics and Gynaecology unit I of Civil Hospital Karachi for the duration of six months from January, 2019 to June, 2019. Subject and Methods: A total of 150 pregnant women attending the antenatal clinic were included in this study. EPDS is the most widely used screening questionnaire for postpartum depression and has been widely validated for not only this condition but also antenatal depression. We chose to regard an EPDS score ≥12 as indicating depression. All information was recorded in predesigned proforma. Results: The average age of the patients was 25.85±4.49 years. Frequency of antenatal depression among pregnant women was 46.67% (70/150). Conclusion: The prevalence of antepartum depression among pregnant women was high and the greatest contributor is the thought of harming herself. We therefore recommended that pregnant women be routinely screened for depression during antenatal care. The necessary psychological care for pregnant women, especially those with risk factors for antenatal depression, should be provided by PCH centers.